A CASE OF PRIMARY SJOGREN`S SYNDROME WITH DISTAL RENAL TUBULAR ACIDOSIS PRESENTING AS HYPOKALEMIC PARALYSIS - PATIL, SANKET; G, PRADHAN; M, SANTOSHI; GITTE, SACHIN (International Journal of Clinical and Biomedical Research, 2016)
Renal tubular acidosis secondary to autoimmune interstitial nephritis is quite common in patients with Sjogren`s syndrome. Here we present a case of 24 year old female who presented with Acute Hypokalemic Quadriparesis and was later diagnosed with distal RTA. Patient did not have features of xerostomia or xerophthalmia but was diagnosed to have Primary Sjogren`s syndrome fromserological findings,in this case renal involvement preceded subjective Sicca syndrome.Patient recovered after giving i.v potassium. Patient was treated with corticosteroids and is asymptomatic during the one year follow up period.